2014
DOI: 10.1002/jsfa.6531
|View full text |Cite
|
Sign up to set email alerts
|

Quality characterization of wheat, maize and sorghum steamed breads from Lesotho

Abstract: BACKGROUND In Lesotho, traditional bread covers different types of dumplings prepared with cereal flour, water, salt and sourdough. This study characterized eight steamed breads prepared from wheat, maize and sorghum. Breads were prepared from both commercial and self‐milled flours according to the procedures followed in rural and urban areas of Lesotho. Descriptive sensory evaluation was conducted to profile sensory properties of the breads. Flour particle sizes, sourdough properties and bread colour, volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…No decay of viscosity, when holding temperature at 95°C, was detected when analysing the different traits, indicating good stability of the starch granules during heating, in consequence, no breakdown was determined. Similar results were also reported by Nkhabutlane et al (2014), who found that steamed maize breads had lower volume, harder and denser crumbs, and their texture was more chewy, dry, fibrous, brittle and needed higher compression force to deform than wheat bread. It would be expected lower breadmaking performance in those populations as Matos & Rosell (2015) found a significant positive correlation between the viscosity increase during cooling and both hardness and cohesiveness of bread crumbs.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…No decay of viscosity, when holding temperature at 95°C, was detected when analysing the different traits, indicating good stability of the starch granules during heating, in consequence, no breakdown was determined. Similar results were also reported by Nkhabutlane et al (2014), who found that steamed maize breads had lower volume, harder and denser crumbs, and their texture was more chewy, dry, fibrous, brittle and needed higher compression force to deform than wheat bread. It would be expected lower breadmaking performance in those populations as Matos & Rosell (2015) found a significant positive correlation between the viscosity increase during cooling and both hardness and cohesiveness of bread crumbs.…”
Section: Resultssupporting
confidence: 89%
“…As the proportion of wheat flour was reduced, the pasting temperature and the baking absorption increased, whereas bread specific volume decreased. Similar results were also reported by Nkhabutlane et al (2014), who found that steamed maize breads had lower volume, harder and denser crumbs, and their texture was more chewy, dry, fibrous, brittle and needed higher compression force to deform than wheat bread. Therefore, bread quality parameters were quite distant from those of wheat or rice, and most of them depend on the maize variety chosen.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A milling method (Dayakar Rao et al, 2016; Wu et al, 2019) showed that 251 and 180 μm were well accepted and that wet grinding reduced the amount of damaged starch, and thus, it was better than bread made with an ultrafine powder. Researchers have tried to reduce these adverse effects on product quality using various treatment methods and have already increased buckwheat (Fang, Qing, Yu, Gu, & Wang, 2014; Lin, Liu, Yu, Lin, & Mau, 2009), quinoa (Wang, Opassathavorn, & Zhu, 2015), sorghum (Nkhabutlane, Rand, & Kock, 2014), and chia seed (Zhu & Chan, 2018) inclusions as additives for steamed bread. Due to the popularity of traditional dietary basis and new demands by numerous consumer groups, this research laid the foundation for the further study of millet steamed bread.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, bread consumption has increased however, increase in bread price from high importation has made bread unaffordable to many households (Sasson, 2012). Studies that explore the possibility of partly substituting wheat with locally grown crops have been done using sorghum (Sorghum bicolour) and millet Abbreviations SLV-Specific loaf volume (Abdelghafor et al2011), sweet potatoes (Ijah et al 2014), rice (Rai et al 2012), maize and sorghum (Nkhubutlane et al 2014). However, the newly produced sorghum genotype EUS130 and proportions below 5 have not been studied in the baking industry.…”
Section: Introductionmentioning
confidence: 99%